Converging humanitarian technology and social work in a public health crisis: a social innovation response to COVID-19 in Hong Kong. Issue 1 (2nd January 2021) - Chui, Cheryl Hiu-Kwan; Ko, Albert
ABSTRACT: Public health crises disproportionately affect vulnerable population groups. Interventions aimed at curtailing the spread of diseases or improving the overall health of the population must aim to reduce existing inequalities rather than exacerbate them. Drawing on social innovation and asset-based community development literature, this article describes the design principles of a project utilising humanitarian technology for disinfectant and sanitation purposes in light of the COVID-19 pandemic. It provides insights into the merits of cross-sector collaboration, particularly between social work and engineering, in effectively addressing the health and sanitation needs of low-income families living in subdivided units in Hong Kong. The project underscores the potential of social innovation in addressing the needs of the vulnerable communities in public health crises.